Talcum induced pneumoconiosis following inhalation of adulterated marijuana, a case report - Scheel Andreas; Krause Daniel; Haars Helmut; Schmitz Inge; Junker Klaus (BMC, 2012)
Abstract Background Talcosis, a granulomatous inflammation of the lungs caused by inhalation of talcum dust, is a rare form of pneumoconiosis. Besides inhalative occupational exposure, intravenous abuse of adulterated drugs is a major cause for this condition. Minerals such as talcum (magnesium silicate) and sand (predominant silicon dioxide) are used to increase both volume and weight of illicit substances. In intravenous heroin-abuse, talcosis is a well-known complication. Here we describe a case of talcosis caused by inhalative abuse of adulterated marijuana. Clinical history A 29-year old man presented with persistent fever, dyspnea and cervical emphysema. He admitted consumption of 'cut' marijuana for several years, preferentially by water pipe smoking. Morphologic findings Lung-biopsies showed chronic interstitial lung disease, anthracotic pigments and birefringent material. Energy dispersive x-ray spectroscopy revealed silicon-containing particles (1-2 μm) and fine aluminum particles (< 1 μm), magnesium and several other elements forming a spectrum compatible with the stated water pipe smoking of talcum-adulterated marijuana. Conclusions The exacerbated chronic interstitial lung disease in a 29-year old patient could be attributed to his prolonged abuse of talcum-adulterated marjuana by histopathology and x-ray spectroscopy. Since cannabis consumption is widely spread among young adults, it seems to be justified to raise attention to this form of interstitial pulmonary disease. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnomx.eu/vs/krause/html/start.html.